Локализация узлового навигационного пункта Азиатского Боспора – Корокондамы - Шамрай, А.Н. (Боспорские исследования, 2009)
On the grounds of the analysis of all sources the author considers there is archaeologically authentic spatial complex of a vast ancient coastal settlement near Tuzla Cape. All territorial elements of the settlement fit in it harmoniously. One can state that the settlement Korokondama served as the main navigation point of the Bosporus and was situated just in the south-eastern corner of the strait near present-day Tuzla Cape. Pseudo Arryan pointed out the settlement lay on a narrow isthmus - a sand spit between the lake of the same name and the sea - the strait. Today the ancient spit together with remains of the settlement is located on1 the seabed in the strait along a sand bank of the Lake Tuzla.